Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1111/j.1540-8175.2005.00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Aortic Regurgitation by Live Three‐Dimensional Transthoracic Echocardiographic Measurements of Vena Contracta Area: Usefulness and Validation

Abstract: In this report, we evaluate 56 consecutive adult patients who underwent standard two-dimensional (2D) and live three-dimensional transthoracic echocardiography (3D TTE), as well as left heart catheterization with aortography (45 patients) or cardiac surgery (11 patients), for evaluation of aortic insufficiency. Similar to the method we previously described for mitral insufficiency, aortic regurgitant vena contracta area (VCA) was obtained by 3D TTE by systematic and sequential cropping of the acquired 3D TTE d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 13 publications
(38 reference statements)
0
80
0
Order By: Relevance
“…113 Three-dimensional echocardiographic color Doppler also allows visualization, and measurement of multiple jets were feasible and correlated morphologically with surgical findings. 113 However, the practical impact is limited, because this study used electrocardiographically gated 3D color flow imaging, whereas real-time volume color flow Doppler imaging is necessary to truly evaluate the feasibility and accuracy of quantification of aortic regurgitation in three dimensions. Three-dimensional TTE and TEE assessments of the aortic valve should be incorporated when available into the assessment of aortic stenosis and to elucidate the mechanism of aortic regurgitation.…”
Section: Quantification Of Aortic Regurgitationmentioning
confidence: 99%
“…113 Three-dimensional echocardiographic color Doppler also allows visualization, and measurement of multiple jets were feasible and correlated morphologically with surgical findings. 113 However, the practical impact is limited, because this study used electrocardiographically gated 3D color flow imaging, whereas real-time volume color flow Doppler imaging is necessary to truly evaluate the feasibility and accuracy of quantification of aortic regurgitation in three dimensions. Three-dimensional TTE and TEE assessments of the aortic valve should be incorporated when available into the assessment of aortic stenosis and to elucidate the mechanism of aortic regurgitation.…”
Section: Quantification Of Aortic Regurgitationmentioning
confidence: 99%
“…3D color Doppler echocardiography is a useful tool in the visualization of the actual shape of the regurgitant orifi ce (vena contracta area) [22][23][24][25]. Khanna et al [22] investigated the accuracy of the vena contracta area measurements by live 3D color Doppler echocardiography in mitral regurgitation.…”
Section: Evaluation Of Regurgitant Orifi Ce In 3d Viewmentioning
confidence: 99%
“…Several studies demonstrated the advantage of using 3D TTE datasets to optimally identify a cross-sectional plane through the vena contracta perpendicular to the aor tic regurgitant flow [108,109]. Using angiographic grading for reference, Fang et al [108] found good agreement for 3D vena contracta area measurements with aortic regurgitation severity grades and proposed a vena contracta area of <20 mm 2 and >60 mm 2 to define mild and severe aortic regurgitation, which has also been referenced in recent guidelines [11]. In a study with similar design, Chin et al [109] also found good agreement of 3D vena contracta measurements with angiographic grading and derived a cutoff value for VCA of <30 mm 2 predicting mild aortic regurgitation and >50 mm 2 for predicting severe aortic regurgitation.…”
Section: Chapter 7 · Valvular Heart Disease -Insufficienciesmentioning
confidence: 99%